Neonatal hippocampal lesions in rhesus macaques alter the monitoring, but not maintenance, of information in working memory - Heuer, Eric (2011)
Neonatal hippocampal damage in rodents impairs medial prefrontal working memory functions. To examine whether similar impairment will follow the same damage in primates, adult monkeys with neonatal hippocampal lesions and sham-operated controls were trained on two working memory tasks. The Session Unique-Delayed Non-Match-to-Sample (SU-DNMS) measures maintenance of information in working memory mediated by the ventral lateral prefrontal cortex. The Object Self-Ordered Task (Obj-SO) measures monitoring of information in working memory mediated by the dorsolateral prefrontal cortex. Adult monkeys with neonatal hippocampal lesions performed as well as sham-operated controls on SU-DNMS at either the 5 or 30s delays, but were severely impaired on the Obj-SO task. These results extend the earlier findings in rodents by demonstrating that early lesions of the hippocampus in monkeys impair working memory processes known to require the integrity of the dorsolateral prefrontal cortex, while sparing lower-order working memory processes, such as recency. Although the present results suggest that the lack of functional hippocampal inputs may have altered the maturation of the dorsolateral prefrontal cortex, future studies will be needed to determine whether the nature of the observed working memory deficit is due to an absence of the hippocampus, a maldevelopment of the dorsolateral prefrontal cortex or both.